ANALISIS ECONOMIC ORDER QUANTITY, SAFETY STOCK DAN REORDER POINT TERHADAP EFISIENSI BIAYA PERSEDIAAN PRODUK DOWNY PADA PT LAUT TIMUR ARDIPRIMA DI TANJUNG REDEB - Purwanto, Sayugo Adi; Jumiyati, Jumiyati (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
One method of the  inventory control effort is the EOQ method usage. The application of safety stock to avoid the risk of running out of inventory and reorder points to determine the right time to reorder.The objective of the study was to find out, analyze and describe the effect of EOQ, the application of safety stock and reorder point on downy product inventory cost efficiency on PT Laut Timur Ardiprima in Tanjung Redeb. The analytical instrument of this research were: normality test, multicollinearity test, autocorrelation test, multiple linear regression analysis, determination coefficient, F test and t test.            The results shown that economic order quantity, safety stock and reorder point simultaneously had a significant influence on the inventory cost efficiency of Downy's products at PT Laut Timur Ardiprima, this was evidenced by the results of the F test where F-count was greater than F-table ( 8,305,138> 10.13) and a significant value of 0.008 <0.05. Economic order quantity (EOQ), Safety stock, and Reorder point partially have a significant effect on Downy product inventory cost efficiency in PT Laut Timur Ardiprima, this was evidenced by the results of the t test where t-count is greater than the respective t-table respectively (53,954> 12,706), (37,909> 12,706) and (-40,723 <-12,706) and the significance values ​​of 0,012 <0,05, 0,017 <0,05, and 0,016 <0,05.